Filsafat Ilmu sebagai Dasar dan Arah Pengembangan Sistem Hukum di Indonesia - Lindra Darnela (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Philosophy of science that seem very theoretical, it is necessary to be able to greatly contribute to the practical needs of the community in building a better legal and in accordance with the ideals of law society toward justice. Philosophy of science could be "spirit" by providing guidance on the values of goodness and truth which is owned by the proper elements in the legal system, namely: the development of the legal structure, legal substance and legal culture. The role of philosophy of science is certainly represented by the scientists in the field of philosophy and law, each of which provide input in every three elements making earlier. This paper discusses the influence of philosophy of science in the development of the legal system in Indonesia.